Private hegemony devices and implementation of the national common curricular base in the municipal public education system of Paraná State (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This paper contemplates the implementing process of the National Common Curricular Base (BNCC in its Portuguese acronym) in the municipal public education networks of Paraná, focusing on Private Hegemony Apparatuses (PHAs), as well as the role played by the State Secretariat of Education (SEED/PR) and the National Union of Municipal Education Directors (UNDIME/PR) in this process. Gramsci contributes with theoretical and methodological support that makes it possible to understand the State as integral, constituted by political society and civil society. In this State Model, the PHAs are allocated, considered institutes, associations and political parties around which the collective aspirations of the rising group are organized. As a result, the PHAs Instituto Reúna and Movimento Colabora Educação (MCE) are understood in connection with large conglomerates, among them the Lemann Foundation (LF), which have been dedicated to implementing the BNCC in Paraná municipalities. This is bibliographic and documentary research with searches on websites of the SEED/PR, National Union of Municipal Education Directors (UNDIME), UNDIME (PR), Movimento pela Base (MPB), as well as data and news regarding the topic. It was clear that UNDIME/PR, SEED/PR and the Municipal Education Secretariats legitimized the process, producing consensus and validating private participation through seminars, live broadcasts and teacher training, offering and indicating inputs organized by these institutes.Keywords: Private Hegemony Apparatuses. Municipal Public Education Networks of Paraná. BNCC.